Effect of an Er,Cr:YSGG Laser on the Debonding of Lithium Disilicate Veneers With Four Different Thicknesses - Giraldo, Hernán; Castaño Gómez, Juliana; López Guerrero, Angela Natalia; Muñoz Fernández, Johanna (Journal of Lasers in Medical Sciences, 2020)
Introduction: The objective of this study was to compare in vitro the resistance and type of failure in the debonding of lithium disilicate veneers with four different thicknesses using an erbium chromium yttrium-scandium gallium-garnet (Er, Cr: YSGG) laser. Methods: Sixty-eight bovine teeth were used to bond round lithium disilicate veneers with a 6-millimeter diameter and four different thicknesses: group 1 (0.4 mm), group 2 (0.8 mm), group 3 (1.2 mm), and group 4 (1.6 mm). Each sample was irradiated with an Er, Cr: YSGG laser with 4 W of power and a frequency of 50 Hz, during 60 seconds, scanning concentrically. The energy density per pulse or fluency applied was 5.33 J/cm2 for the four groups. The samples were subjected to a force in a universal testing machine and then observed under a microscope to determine the type of failure. Data were statistically analyzed with the non-parametric Kruskal-Wallis test. Results: The tendency in the results revealed that the thicker veneers showed more resistance to the debonding process. The debonding strength for group 3 was the highest (5.62 MPa), followed by group 4 (5.20 MPa), then group 2 (0.85 MPa), and finally group 1 (0.0 MPa). The most frequent type of failure was a cohesive failure in cement (CC) for all groups, with 73.53% (P ≤ 0.083). Conclusion: Er, Cr: YSGG laser irradiation influences the debonding of lithium disilicate veneers with different thicknesses: the smaller thickness showed the greater debonding. The thickness of veneers was not associated with the type of failure.